Developing Knowledge of Inquiry-Based Teaching by Analysing a Multimedia Case: One Study with Prospective Mathematics Teachers - Oliveira, Hélia (2013)
This study aims to understand the knowledge of inquiry-based teaching that prospective mathematics teachers reveal when analysing a multimedia case featuring one mathematics teacher´s practice in one 7th grade lesson. Data analysis focused on individual reflections that prospective teachers had written, covering four major points: the nature of the task, articulation and purpose of the lesson phases, the teacher’s role in inquiry-based teaching, and anticipated challenges. The results show that the use of the multimedia case enabled prospective teachers to develop an understanding of various dimensions of inquiry teaching practice and its complexity, while they simultaneously began to predict specific difficulties they would face in their future professional practice. Significant elements of a dialogical perspective of learning also emerged from the study, as the prospective teachers recognize the central roles of language in knowledge construction, and of the interaction between teacher and student and among the students, in different moments of the lesson.